Influencia del espesor del tape de semillas sobre la germinación y desarrollo del cultivo de maíz (Zea mays L.), en la zona de Babahoyo - Sucunuta Reina, Tyrone Antonio (2017)
VIII. SUMMARY The present research work was carried out outside the Laboratory of Soils of the Faculty of Agricultural Sciences of the Technical University of Babahoyo, located in Km 7.5 of the Babahoyo-Montalvo road, with geographical coordinates 79º 32' of western length And 1 49 'south latitude. According to the climatological classification of Köppen the area presents a humid tropical climate; Altitude of 8 msnm, average precipitation of 2167.7 mm, with average annual temperature of 26.3 0C, with monthly average heliophania of 75.7 and a relative humidity of 89%. The soil is flat topography, clay-loam texture and regular drainage. The PIONNER 30F35 maize hybrid was used as seed material. The objectives were to evaluate the germination of the maize crop to different thicknesses in the seed tape and to determine the effects of the thickness of the tape in the development of the maize crop. The treatments were conformed the seed tape at different depths, 3, 6, 9, 12, 15 and 18 cm. We used the Completely Random Blocks design, with six treatments and three replicates. The treatments were the seeding depths. For the separation of the means was used the Tukey test at 95% confidence. Three wood chambers with five alveoli (3 rows and 3 columns) were used for the experiments and a soil substrate was prepared. The evaluations were carried out from the third day of planting with intervals of frequency of two days, until the 30 days, that the germination process must finish. The evaluated data were percentage of germination, stem length, leaf emission, wet weight and dry weight of roots. From the results, it was determined that in the present investigation, if the influence of the thickness of the seed tape was obtained on the germination of the maize crop in the Babahoyo area; The depth of soil with depth of 3 cm facilitates the process of germination of the seed with 100%; The length of the stem obtained a marked difference between the thickness of tape of depths of 6 cm and 12 cm; Foliar emission reached good results when the depth of the tape was 3 cm, decreasing as the depth of the seed tape increased and the wet and dry weight of roots presented good results with the tape depth of 3 cm.